Iodine‐Catalyzed Regioselective Sulfenylation of Indoles with Thiols in Water. Issue 8 (6th June 2016) - He, Yongqin; Liu, Shengkang; Wen, Ping; Tian, Wanfa; Ren, Xiaoyu; Zhou, Qiangxiao; Ma, Haojie; Huang, Guosheng
Abstract: A novel protocol of Iodine catalyzed oxidative 3‐sulfenylation of indoles with thiols has been developed using cheap and environment friendly Hydrogen peroxide (30 % H2 O2 ) as oxidant. In addition, H2 O was firstly used as solvent in this type of reaction, in this method, indoles react with multiple thiols smoothly and various 3‐sulfanylindoles were obtained in good to excellent yields.. The extensive scope of substrates, the mild reaction conditions, and the high selection of reaction site delivery promising applications in drug discovery and functional materials. Especially, Indole‐1‐carboxamides were also compatible with this transformation, and the predictable products were obtained in good yields. Abstract : An Iodine catalyzed oxidative 3‐sulfenylation of indoles with thiols has been developed using cheap and environment friendly Hydrogen peroxide (30 % H2 O2 ) as oxidant. H2 O was firstly used as solvent in this type of reaction. In addition, indoles react with multiple thiols smoothly and various 3‐sulfanylindoles were obtained in good to excellent yields. The extensive scope of substrates, the mild reaction conditions, and the high selection of reaction site delivery promising applications in drug discovery and functional materials.